IN VITRO DETERMINATION OF MINIMUM LENGTH PENETRATION OF A 27G MONOJECT NEEDLE TO IRRIGATE THE MAIN CANAL, AVOIDING EXTRUSION - Marchant, Carlos; Aguirre, Fernando; Márquez, Eduardo; Tapia, Marcelo (Applied Sciences in Dentistry, 2020)
Objective: To determine the minimum length penetration required of a monoject27G needle to irrigate the main canal, avoiding extrusion. Materials and methods: 52 teeth were used, decoronated and worked at equal lengths at a MAF 40. They were randomly assembled in 3 molds and irrigated with diluted Omnipaque. Central trend values were calculated using descriptive statistics. Barlett, Shapiro Wilk and ANOVA one-way tests were applied to analyze statistically significant differences. Subsequently the logistic regression of Oswell-Lemeshow was calculated to look for causality between variables. Results: Statistically significant results show that at higher needle penetration, the probability of extrusion is greater; regarding minimal length penetration to prevent extrusion, the safest length to irrigate is working length (WL) -4mm. Conclusions: The minimum length penetration to irrigate preventing extrusion is WL-4 mm.